Effect of selenium nanoparticles on the quality and fertility of short-term preserved boar semen - Paul, Dipan Rudra; Talukdar, Dibyajyoti; Ahmed, Fazal Ali; Lalrintluanga, K.; Kalita, Girin; Tolenkhomba, T. C.; Chakravarty, Himsikha; Katiyar, Rahul; Khargharia, Gautam; Deori, Sourabh (Frontiers in Veterinary Science, 2024)
This study was carried out to investigate the effect of different concentrations of selenium nanoparticles (Se-NPs) in the Beltsville Thawing Solution (BTS) extender on the semen quality and fertility of Hampshire crossbred pigs. For the study, semen was collected from four boars (10 ejaculates/boar) by the gloved hand method. Each ejaculate was extended @ 1:2 with the BTS extender and split into four aliquots. The control (C) samples were without the supplementation of Se-NPs, whereas the other three were supplemented with 0.5 (T1), 1 (T2), and 2 μg ml−1 of Se-NPs (T3) and stored at 15°C in a BOD incubator. Extended semen was evaluated at 0 (immediately after dilution), 24, 48, 72, and 96 h of storage for sperm motility, live sperm, plasma membrane integrity, acrosome integrity, DNA integrity, and mitochondrial membrane potential (MMP). The mean percentage of sperm motility, live sperm, and sperm with intact plasma membrane and acrosome, and MMPs were significantly (p < 0.01) higher in all treated groups in comparison to control at 24, 48, 72, and 96 h of storage. Sperm with intact DNA in all treated groups increased significantly at 48 (p < 0.05), and 72 and 96 (p < 0.01) h of storage in comparison to the control group. The concentration of 1 μg ml−1 of Se-NPs was found to be the best among other concentrations. In each group, 10 sows were artificially inseminated with the liquid semen preserved for 72 h at 15°C. Supplementation of 1 μg ml−1 of Se-NPs yielded the highest conception rate in comparison to other groups. In conclusion, supplementation of 1 μg ml−1 of Se-NPs in the BTS extender resulted in the best semen quality and conception rate during the short-time liquid preservation of boar semen.